Protection against Experimental Melioidosis following Immunisation with a Lipopolysaccharide-Protein Conjugate. (7th May 2014) - Scott, Andrew E.; Ngugi, Sarah A.; Laws, Thomas R.; Corser, David; Lonsdale, Claire L.; D'Elia, Riccardo V.; Titball, Richard W.; Williamson, E. Diane; Atkins, Timothy P.; Prior, Joann L.
Abstract : Melioidosis is a severe infectious disease caused by Burkholderia pseudomallei . It is refractory to antibiotic treatment and there is currently no licensed vaccine. In this report we detail the construction and protective efficacy of a polysaccharide-protein conjugate composed of B. pseudomallei lipopolysaccharide and the H c fragment of tetanus toxin. Immunisation of mice with the lipopolysaccharide-conjugate led to significantly reduced bacterial burdens in the spleen 48 hours after challenge and afforded significant protection against a lethal challenge with B. pseudomallei . The conjugate generated significantly higher levels of antigen-specific IgG1 and IgG2a than in lipopolysaccharide-immunised mice. Immunisation with the conjugate also demonstrated a bias towards Th1 type responses, evidenced by high levels of IgG2a. In contrast, immunisation with unconjugated lipopolysaccharide evoked almost no IgG2a demonstrating a bias towards Th2 type responses. This study demonstrates the effectiveness of this approach in the development of an efficacious and protective vaccine against melioidosis.